2019
DOI: 10.1007/s11606-018-4784-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Conflict of Interest, Disclosure Status, and Relevance on Medical Research from the United States

Abstract: BACKGROUND: Financial interactions between industry and healthcare providers are reportable. Substantial discrepancies have been detected between industry and selfreport of these conflicts of interest (COIs). OBJECTIVE: Our aim was to determine if authors who fail to disclose reportable COI are more likely to publish findings that are favorable to industry than authors with no COI. DESIGN: In this blinded, observational study of medical and surgical primary research articles in PubMed, 590 articles were review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 15 publications
(18 reference statements)
2
28
1
Order By: Relevance
“…Our results indicate that, in autism early intervention research, the presence of the COI types we coded is similar to other fields that have extended effort toward accounting for COIs in published literature (Cherla et al, 2019; Okike et al, 2009). Interestingly, several COIs appear to be associated with one another.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our results indicate that, in autism early intervention research, the presence of the COI types we coded is similar to other fields that have extended effort toward accounting for COIs in published literature (Cherla et al, 2019; Okike et al, 2009). Interestingly, several COIs appear to be associated with one another.…”
Section: Discussionsupporting
confidence: 75%
“…In research fields such as medicine, public health, substance abuse prevention, and criminology, meta‐analyses have been conducted to investigate the influence of COIs on effect sizes reported in intervention studies. This work has shown that studies conducted by researchers with COIs are more likely to show positive findings than studies conducted by researchers who do not have COIs (Cherla et al, 2019; Chivers, 2019; Delgado & Delgado, 2017; Wells, 2017). In the medical field, where COIs have the longest history of being reported and investigated, COIs are considered ubiquitous and disclosure rates are around 70% of all published studies.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Financial relationships between authors and industry has been shown to improve published outcomes in favor of industry partners. 19 These results suggest that future research, which minimizes or removes potential sponsorship bias, may have a role in improving the quality of evidence related to anticoagulation therapy.…”
Section: Discussionmentioning
confidence: 94%
“…All publication originated from Organisation for Economic Co-operation and Development (OECD) member countries. The United States had the largest contribution (43), followed by Canada (19), United Kingdom (10), and The Netherlands (8).…”
Section: Country Of Publicationmentioning
confidence: 99%